问题 解答题
怎样简便就怎样算
[1-(
1
4
+
3
8
)]÷
1
4
13÷25%÷4
2
9
+
1
2
÷
4
5
+
3
8
8
13
÷7+
1
7
×
6
13
12
5
×(
5
6
+
3
4
)+
4
5
10÷
2
9
+
1
6
×4
7
9
÷
11
5
+
2
9
×
5
11
1
6
×
2
3
÷(
4
5
-
8
15
1
12
+
1
2
-
7
12
)÷
1
7
44×
2
43
答案

[1-(
1
4
+
3
8
)]÷
1
4

=(1-

5
8
)×4,

=

3
8
×4,

=

3
2

=1

1
2
8
13
÷7+
1
7
×
6
13

=

8
13
×
1
7
+
1
7
×
6
13

=

1
7
×(
8
13
+
6
13
),

=

1
7
×
14
13

=

2
13
7
9
÷
11
5
+
2
9
×
5
11

=

7
9
×
5
11
+
2
9
×
5
11

=

5
11
×(
7
9
+
2
9
),

=

5
11
×1,

=

5
11
44×
2
43

=(43+1)×

2
43

=43×

2
43
+1×
2
43

=2+

2
43

=2

2
43
13÷25%÷4,

=13÷(25%×4),

=13÷1,

=13;

12
5
×(
5
6
+
3
4
)+
4
5

=

12
5
×
5
6
+
12
5
×
3
4
+
4
5

=2+

9
5
+
4
5

=2+2

3
5

=4

3
5

1
6
×
2
3
÷(
4
5
-
8
15
),

=

1
9
÷(
12
15
-
8
15
),

=

1
9
÷
4
15

=

1
9
×
15
4

=

5
12

2
9
+
1
2
÷
4
5
+
3
8

=

2
9
+
1
2
×
5
4
+
3
8

=

2
9
+
5
8
+
3
8

=

2
9
+1,

=1

2
9

10÷

2
9
+
1
6
×4,

=10×

9
2
+
2
3

=45+

2
3

=45

2
3

1
12
+
1
2
-
7
12
)÷
1
7

=(

1
12
+
6
12
-
7
12
)÷
1
7

=0÷

1
7

=0.

问答题 简答题
问答题 论述题